Estrogen, progesterone, and human epidermal growth factor receptor 2 discordance between primary and metastatic breast cancer - Walter, Vincent P.; Fischer, Chiara; Deutsch, Thomas M.; Ersing, Catherine; Nees, Juliane; Schütz, Florian; Fremd, Carlo; Grischke, Eva-Maria; Sinn, Peter; Brucker, Sara; Schneeweiss, Andreas; Hartkopf, Andreas; et al. (Breast cancer research and treatment, 2020)
The estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) statuses are frequently discordant between the primary tumor and metastatic lesions in metastatic breast cancer. This can have important therapeutic implications.
Gesehen am 08.12.2021